Effect of post-harvest loss reduction practices on household food security of cowpea farmers in Niger and Nasarawa States, Nigeria - Tosin Olawoye; Moradeyo Adebanjo Otitoju; Olaide Oluwafemi Olawoye (Indonesian Journal of Agricultural Research, 2026)
This study evaluated the influence of post-harvest loss reduction procedures (PHLRP) on the food security of cowpea farmers in Niger and Nasarawa States, Nigeria. A multistage sampling procedure was utilized, resulting in the random selection of 216 cowpea producers from six local government areas, with 108 respondents from each chosen state. Descriptive and inferential statistics, including the household food insecurity access scale (HFIAS) and ordered logit models, were employed to assess food security status and evaluate the influence of post-harvest loss reduction methods on food security outcomes. The HFIAS analysis indicated that nearly all cowpea farmers in the study area experienced food insecurity, highlighting the contradiction of food insecurity among households that are primary producers of a vital food crop. Results of the marginal effect showed that the use of pirimiphos-methyl was positive and significantly enhanced the possibility of household food security (p < 0.01). In contrast, granary storage (p < 0.05) and training access (p < 0.10) were significant but reduced the probability of food security among the cowpea farmers. This paper provides empirical information regarding the significance of adaptable PHLRP on enhancing food security for smallholder cowpea farmers, presenting practical policy recommendations for agricultural extension and rural development initiatives in Nigeria. Major constraints faced by the cowpea farmers were the high cost of improved storage materials and high transportation costs. The study, recommends making Purdue-improved cowpea bags readily available to reduce post-harvest losses, while encouraging farmers to form cooperatives to share transportation costs.